Describing gonad development and gametogenesis in southern Africa's endemic box jellyfish Carybdea branchi (Cubozoa, Carybdeidae). Issue 1 (2nd January 2019) - Mohamed, R; Skrypzeck, H; Gibbons, MJ
Abstract : Information on the reproductive development of species of box jellyfish (class Cubozoa) is poor globally, despite their significance as potent stingers and worrying projections about range expansions. While most species are confined to tropical and subtropical waters, the South African box jellyfish Carybdea branchi is commonly found in the cold-water (especially southern) Benguela ecosystem. Its biology is unknown. Here, we examine reproductive development and describe gametogenesis in this dioecious species. Four and five maturity classes were determined for males and females, respectively, as well as five oocyte developmental stages. Oocyte sizes differed significantly between developmental stages. Mature and immature medusae differed significantly in size, but males and females did not. Individuals matured at approximately 30 mm average bell dimensions. Carybdea branchi displayed gonadal development characteristic of a semelparous organism.